Subchronic intranasal lipopolysaccharide exposure induces pulmonary autoimmunity and glomerulonephritis in NZBWF1 mice - Lauren K. Heine; Lichchavi D. Rajasinghe; James G. Wagner; Ryan P. Lewandowski; Quan-Zhen Li; Alexa L. Richardson; Ashleigh N. Tindle; Jenan J. Shareef; Jack R. Harkema; James J. Pestka (Taylor & Francis Group, 2024)
Lupus, a systemic autoimmune disease shaped by gene-environment interplay, often progresses to endstage renal failure. While subchronic systemic exposure to bacterial lipopolysaccharide (LPS) triggers autoimmunity and glomerulonephritis in lupus-prone mice, it is unknown if inhaling LPS, which is common in certain occupations, can similarly trigger lupus. Here we determined how subchronic intranasal (IN) LPS instillation influences autoimmunity and glomerulonephritis development in lupusprone NZBWF1 female mice. Briefly, mice were IN-instilled with vehicle or E. coli LPS (0.8 μg/g) twice weekly for 5 wk, followed by necropsy. For systemic comparison, additional cohorts of mice were injected with LPS intraperitoneally (IP) using identical doses/timing. Lungs were assessed for inflammatory and autoimmune responses and then related to systemic autoimmunity and glomerulonephritis. IN/LPS exposure induced in the lung: i) leukocyte infiltration, ii)mRNA signatures for cytokines, chemokines, IFN-regulated, and cell death-related genes, iii) ectopic lymphoid tissue formation, and iv)diverse IgM and IgG autoantibodies (AAbs). Pulmonary effects coincided with enlarged spleens, elevated plasma IgG AAbs, and inflamed IgG-containing kidney glomeruli. In contrast, IP/LPS treatment induced systemic autoimmunity and glomerulonephritis without pulmonary manifestations. Taken together, these preclinical findings suggest the lung could serve as a critical nexus for triggering autoimmunity by respirable LPS in genetically predisposed individuals.